Variant analyses of candidate genes in orofacial clefts in multi‐ethnic populations. (21st June 2021) - Li, Mary; Olotu, Joy; Buxo‐Martinez, Carmen J.; Mossey, Peter A.; Anand, Deepti; Busch, Tamara; Alade, Azeez; Gowans, Lord J. J.; Eshete, Mekonen; Adeyemo, Wasiu L.; Naicker, Thirona; Awotoye, Waheed O.; et al.
Abstract: Objectives: Cleft lip with/without cleft palate and cleft palate only is congenital birth defects where the upper lip and/or palate fail to fuse properly during embryonic facial development. Affecting ~1.2/1000 live births worldwide, these orofacial clefts impose significant social and financial burdens on affected individuals and their families. Orofacial clefts have a complex etiology resulting from genetic variants combined with environmental covariates. Recent genome‐wide association studies and whole‐exome sequencing for orofacial clefts identified significant genetic associations and variants in several genes. Of these, we investigated the role of common/rare variants in SHH, RORA, MRPL53, ACVR1, and GDF11 . Materials and Methods: We sequenced these five genes in 1255 multi‐ethnic cleft lip with/without palate and cleft palate only samples in order to find variants that may provide potential explanations for the missing heritability of orofacial clefts. Rare and novel variants were further analyzed using in silico predictive tools. Results: Ninteen total variants of interest were found, with variant types including stop‐gain, missense, synonymous, intronic, and splice‐site variants. Of these, 3 novel missense variants were found, one in SHH, one in RORA, and one in GDF11 . Conclusion: This study provides evidence that variants in SHH, RORA, MRPL53, ACVR1, and GDF11 may contribute to risk of orofacial clefts in various populations.